Ethical implications of cross-cultural international art therapy. (November 2017) - Potash, Jordan S.; Bardot, Heidi; Moon, Catherine Hyland; Napoli, Michelle; Lyonsmith, Angela; Hamilton, Megan
Highlights: International art therapy collaborations entail cultural humility, decolonizing, supervision. International work involves culturally appropriate studio, materials, creative processes. International art therapy ensures accountability, commitment, respectful power sharing. Abstract: Art therapists are increasingly offering their services in international contexts. Although usually altruistic in nature, unexamined practices can result in detrimental consequences to both the travelers and host communities. A consideration of the ethical dilemmas that one might face can better orient art therapists to the many aspects of offering art therapy abroad. Preparation for cross-cultural work in international contexts entails assessing motivations, developing cultural competence, and ensuring sustainable practices. While in country, there are considerations pertaining to art materials, studio space, service delivery, artworks, roles, positions of power, and consent. Throughout the experience, examination of accountability to multiple stakeholders, including through reporting and fund-raising, is crucial. A critical look at the ethics and values involved in providing art therapy internationally can help ensure that art therapists offer global services with integrity.